Impact of seawater and canopy cover on the phyllosphere bacterial community of Rhizophora mucronata leaves - Asnat, Soudjay; Fahimat, Said Hassane; Ahmed, Allaouia Allaoui Said; Mohamed, An-icha; Abdou, Nemati Mohamed; Ismail, Soifiata Said; Karima, Youssouf Abdou; Sailine, Raissa; Aladine, Boundjadi Hamdane; Mohamed, Nadjim Ahmed; Elyamine, Ali Mohamed (International Journal of Advanced Engineering Research and Science, 2022)
The plant-microorganism interaction is a well-studied topic in the world of science due to the sustainable management of the ecosystems. The phyllosphere remains the habitat of some microorganisms where several interactions take place. In order to assess whether the mangrove leaves can harbor a bacterial population and analyze the abundance in these leaves microbiotas, leaf samples of mangroves species (Rhizophora mucronata) were collected in the mangroves of Ouroveni in East-Mbandjini, Grande-Comoros. Through the 16S rRNA genes sequencing, the results showed that in the different experimental group, 105303, 110873, 124703, 146954 and 112225 OTUs were identified respectively, where the canopy was open (C1), semi-open (C2), completely closed (C3), and where the plants are submerged (S) and non-submerged (NS) in seawater. The identified OTUs was positively correlated with leaves-wax (p < 0.05, r2 = 0.91), nitrogen (r2 = 0.72), phosphorus content (r2 = 0.62) and the factor “seawater” (r2 = 0.93). It was however highly and negatively correlated with the canopy cover (r2 = 0.93). Considering the factor "seawater", the relative abundance of bacteria in the submerged leaves was significantly higher compared to that from the non-submerged plants. By taking into account the factor “canopy cover”, it was revealed that more the canopy cover was open, the less was the relative abundance of bacteria. Thus, the finding of this present study affirm that the leaves of mangroves can be a major habitat to host a large population of bacteria that can be influenced by local abiotic factor.